Determinants of Tobacco Consumption in Papua New Guinea: Challenges in Changing Behaviours. Issue 2 (May 2015) - Hou, Xiaohui; Xu, Xiaochen; Anderson, Ian
Abstract: This article analyses smoking prevalence and smoking behaviours in Papua New Guinea (PNG). Using the 2009–2010 PNG Household Income and Expenditure Survey, the article analyses the determinants of tobacco use and tobacco choices in PNG. The results show adults (18 years and above) in the poorest quartile are more likely to smoke. Tobacco consumption imposes a large financial burden to poor households. Tobacco consumption accounts for about 23 per cent of total household food expenditure for households in the poorest quartile, as compared with 15 per cent for the entire sample. However, most of these households consume non‐processed tobacco. The study reveals the urgency to control tobacco consumption in PNG and considers some practical challenges that the country may face.